Concordance of Dermoscopic Findings and Wood’s Lamp Findings in Melasma Patients - Nasar, Amna; Aamir Habib; Qamar Ud Din; Summaya Saleem; Sadaf Jamshaid; Usman Sajid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find the concordance of Dermoscopic and Wood’s lamp findings in melasma patients. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Nov 2020 to Sep 2021. Methodology: A total of sixty patients clinically classified as melasma were enrolled in the study. Clinical assessment was done, and patients were examined with Wood’s lamp and Dermoscope, and findings were recorded. Results: The results of concordance of Wood’s lamp findings and Dermoscopic findings were significant as analysed by Kappa Statistics where value of k was 0.597 and p-value was <0.001. Conclusion: Dermoscopy is a newer and more advanced tool. It should be used as a screening and diagnostic tool for melasma and other pigmentation disorders in our Outpatient Departments for earlier subtyping of melasma, deciding the treatment choice and predicting prognosis.